¿Duermes mucho Tony? Interpersonal and Transactional Uses of L1 in the Foreign-Language Classroom - Sandra Higareda; Georgina López; Gerrard Mugford (Universidad Nacional de Colombia, 2009)
Whilst communicative teaching approaches sanction, often grudgingly, the limited use of the students' first language (L1) in English Language Teaching (ELT), critical debate is now centred on a much more substantial and energetic role for the use of mother tongue in the language classroom. Justifications favouring the use of L1 currently range from ideological arguments to classroom teaching considerations. This paper contributes to this ongoing debate by examining how new generations of language teachers in Mexico are using the students' mother tongue, Spanish, not only as a pedagogical tool but to develop and reinforce interpersonal relationships in the language classroom in order to enhance the learning of English.